Teachers' Performance Improvement Planning and Learning Optimization - Amiruddin Siahaan; Makmur Syukri; Hendriyal Hendriyal; Azhar Azhar (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Improving teacher performance is the upstream of the success of the learning process, and outstanding students are downstream of the process. This study aims to describe planning for improving teacher performance and optimizing learning. This type of research belongs to the category of qualitative approach with literature study method. Study analysis materials and data sources were obtained from internet-based searches with credible pages, such as Google Scholar, DOAJ, Moraref, and SINTA. The data materials in question include books, scientific articles, proceedings, and student final assignments. Furthermore, the validity or validity of the data is checked using data materials (scientific). The results of this study indicate that planning for improving teacher performance and optimizing learning through the stages of greedy organization, work intensification, performativity, and understanding organizational strengths.